Comunicação, consumo e mobilizações contemporâneas : representações midiáticas da multidão em contextos de resistência - Mitraud, Francisco Silva (2017)
The aim of this research is to problematize the mediatic representation of contemporary mobilizations, through an object that we call body-multitude. Our problem is to understand which senses are produced, especially by the printed media, in relation to the multitudes that articulate themselves to resist the hegemonic. For this, we carried out a review of the literature, in order to constitute a cartography of the various concepts about human collectives, from Rome and Greece, to the present day. Since classical antiquity, significant parts of society have been kept apart from power and the state. In contemporary times, authors such as Antonio Negri and Michael Hardt, Maurizio Lazzarato and Paolo Virno, based on the conception of Baruch de Espinoza, reflect on the mobilizations of the late twentieth and early twenty first centuries that confront the hegemonic, and conclude that these multitudes appear as a response and the possibility of new forms of democracy. From this perspective, the multitudes have in the body the essence of their nature, since it is from their plural and heterogeneous character that their biopotential emanates. In the past, the body, in its singularity, could resist and represent a collective - Gandhi and Mandela are both good examples. In postmodernity, its preponderance in the power relations remains, but mobilized to constitute with other bodies the biopotent multitude. To answer our research problem, we created a corpus with photographic images and texts from newspapers, magazines and alternative media that broadcast news about the demonstrations in Brazil in 2013 and 2016. To analyze it we fundamentally used the Theory-method of French discourse analysis, with emphasis on the intericonicity, device proposed by Courtine. The literature review and the corpus make it clear that the senses attributed to the multitude are unstable. Based on the findings, we conclude that, although the contemporary multitude is characterized by its plurality and heterogeneity, at all times there is a displacement of meanings, produced by textual-imagistic compositions, that bind it to previous conceptions and deny its nature and biopotential. The recurrence of these compositions was object of analysis which result is the proposal of six categories. The analysis also reveals an ontological impossibility of the imagetic representation of the multitude and that the printed media not only co-opts their discourses, but also produces meanings antagonistic to their nature, usually linking them to violence and to illegality and disqualifying their objectives.